Rheological and melting properties of sucrose-free dark chocolate - Oba, Sirin; Toker, Omer Said; Palabiyik, Ibrahim; Konar, Nevzat; Goktas, Hamza; Cukur, Yusuf; Artik, Nevzat; Sagdic, Osman (TAYLOR & FRANCIS INC, 2017)
In this study, sugar-free dark chocolate was produced from isomalt and maltitol by (V) seeding technique as an alternative to conventional tempering process. The effect of (V) seed concentrations on the particle size distribution (PSD), textural, rheological and melting properties of the final products were examined and the results were compared with those of conventional sugar-free dark chocolates. For this aim, conched dark chocolates were melted and crystallised with (V) seeds which were added at different concentrations (0.5, 0.6, 0.7, 0.8, 0.9 and 1.0%, m/m). According to the results PSD, hardness, rheological and melting properties were not influenced by seeding technique compared to conventional tempering method. On the other hand, inverse relation was observed between largest particle size and specific surface area of the samples. Hardness values of isomalt and maltitol including samples were found to change between 15.33-18.79N. Casson model best described the flow behaviour of the sugar-free chocolates. As a result, seeding technique can be used as an alternative method in sugar-free dark chocolate production in terms of quality and physical properties.
Keywords: Dark chocolate; Maltitol; Isomalt; Precrystallisation; Texture; PARTICLE-SIZE DISTRIBUTION; MILK CHOCOLATE; COCOA BUTTER; PRECRYSTALLIZATION PROCESS; CRYSTALLIZATION; FORMULATION; EMULSIONS; SYSTEMS; IMPACT; FOOD; Food Science & Technology